Epstein–Barr Virus-Induced Mononucleosis as an Imitator of Severe Preeclampsia - Staley, S. Allison; Smid, Marcela C.; Dotters-Katz, Sarah K.; Stringer, Elizabeth M. (American Journal of Perinatology Reports, 2017)
Background In pregnancy, conditions presenting with hematologic abnormalities, transaminitis, and proteinuria pose diagnostic challenges in pregnancy.Case We present the case of an 18-year-old woman, G1P0, at 33 weeks' gestation with fever of unknown cause, who developed progressively elevated liver enzymes, proteinuria, and thrombocytopenia, due to Epstein–Barr virus (EBV) infection.Conclusion Acute infection with EBV should be included in the differential diagnosis of preeclampsia with severe features, particularly in the setting of fever. Supportive treatment and observation may prevent iatrogenic preterm birth.
Keywords: preeclampsia; mononucleosis; preterm birth; maternal; thrombocytopenia